Analysis of costs and prices of building rehabilitation work in federal university of technology, Minna, Nigeria using in-house consultants - Lawal .P.O, (Penerbit UKM, 2011)
The paper is a detailed analysis of costs and prices of rehabilitation work carried out on some of the Federal University of Technology, Minna buildings on two of its campuses in the last quarter of 2006. Lecturers of the built-environment faculties were the supervising consultants. The aim was to verify the merits of using in-house consultants in place of the conventional ones. Method used in data collection was historical- collecting from the archives of the Task-force (consultants) and percentages was the analytical tool employed. Figures of savings made for the client by the consultants from both the pre-contract estimates and the various contractors’ variation claims were collated and analyzed. It was discovered that savings of between 9 and 43 percents were made on the cost of each of the contracts (lots), culminating in savings of about N9 million. The normal consultancy fee was waived for a flat-rate allowance The further patronage of this type of in-house consultants was recommended for tertiary institutions’ infrastructural facilities rehabilitation work.